Punitive and prosocial reactions to discrimination attributed to implicit bias - Miller, Stuart (Kansas State University, 2023)
Theories of moral judgment suggest that people may respond less punitively and more prosocially to discrimination attributed to implicit, compared to explicit, bias. Additionally, what people believe about the nature of implicit bias may affect their perceptions of the blameworthiness of discrimination caused by implicit bias. The two studies presented here were designed to test these assumptions. In Study 1, participants read a scenario in which a case of racial discrimination was caused by either implicit or explicit bias, and the effects on mental state attributions involved in blame (e.g., awareness, control, intent), as well as how these attributions relate to support for punishment and forgiveness were examined. Study 2 examined how scientific communications about implicit bias affected these judgments by framing implicit bias as something that people are unconscious of and cannot control, or something that people can be aware of and control with effort. Additionally, both studies examined the role of individual differences related to perceptions of bias and discrimination in moderating these effects. Results of these studies were consistent with theories of blame that emphasize the importance of perceptions of intent in attributions of blame. When discrimination was attributed to implicit, compared to explicit bias (Study 1), and when implicit bias was framed as unconscious and uncontrollable, compared to more conscious and controllable (Study 2), the perpetrators’ behavior was perceived as less intentional, blameworthy, and deserving of punishment. The results of Study 1 also suggest that people are more sympathetic toward, and forgiving of, perpetrators who unintentionally discriminate. These findings contribute to our theoretical understanding of moral judgments and have practical implications for the consequences of how scientific knowledge of implicit bias is communicated to the public.
Keywords: Implicit bias; Blame; Moral judgment